Causes of Delays Occurring in Linear Projects-A Survey of Prestressed Concrete Sheet Pile Retaining Wall Constructions in Taiwan - Kuo Chiang Pin; Vo Duy Hai (Slovak Journal of Civil Engineering, 2025)
Delays occur in all types of projects, including those featuring linear works. In the hopes of identifying the major causes of delays in prestressed concrete sheet pile retaining wall projects in Taiwan, we conducted a literature review and pilot study to determine causes of potential delays. The study obtained the “causes of actual delays” by analyzing material supply request records from a pile supplier, which covered 113 completed projects executed from 2019 to 2021. Additionally, “causes of perceived delays” were gathered through 49 Analytical Hierarchy Process (AHP) questionnaires from project parties. The sets of the causes of delays identified from the surveys were ranked using the Relative Importance Index (RII), and the correlation between the ranked sets of “causes of actual delays” and “causes of perceived delays” was assessed using the Spearman rank correlation (ρ). The results showed that the top five critical factors were “acts of God or bad weather”, “mistakes during the construction stage— wrong jobs”, “unrealistic contract durations imposed by clients”, “inadequate path design”, and “poor procurement management by contractors”. The outbreak of the novel coronavirus disease (COVID-19) pandemic did not significantly impact the availability of skilled personnel for the completed projects.